The development of deformation process in carbon fiber reinforced plastics and metals on acoustic emission data - LEKSOVSKIJ, A.M.; PILECKI, S.; GUBANOVA, G.N. (Archives of Acoustics, 1995)
There exists some correlation between deformation curve type and characteristics of acoustic emission flow. It is observed nonhomogeneous development of micro structure changes in the different parts of the specimens on diverse stages of deformation. The collective effects on various scale levels are observed in some local volumes at the concluding period of loading. It is shown that a process of the fracture occurring in some micro volumes of strained composite of the type of carbon fiber reinforced plastic (CFRP), takes place on a few levels of velocity and development times.